Antidiabetic Potential of Emodin in Streptozotocin-Induced Type-2 Diabetic Rats - N, Niveditha; D, Rohini; B, Usharani; C, Shobana (Journal of Neonatal Surgery, 2025)
Diabetes mellitus, particularly type 2 diabetes, is a growing global health issue, often exacerbated by insulin resistance, metabolic disturbances, and inflammatory responses. Emodin, a natural anthraquinone derivative, has been widely recognized for its pharmacological properties, including its antidiabetic potential. This study investigates the therapeutic efficacy of emodin in ameliorating Type 2 diabetes in Wistar albino rats induced by streptozotocin (STZ). Male rats were divided into healthy, diabetic, and treatment groups, with diabetic groups receiving emodin (40 mg/kg body weight/day, orally) or metformin for 45 days. Diabetes induction was confirmed by elevated blood glucose levels, altered lipid profiles, and reduced insulin sensitivity. Emodin administration significantly reduced fasting blood glucose levels and improved glucose tolerance, comparable to metformin treatment. Biochemical analyses revealed that emodin restored the lipid profile, enhanced antioxidant enzyme activity, and suppressed oxidative stress markers in diabetic rats. The study revealed that emodin exhibited antidiabetic effects by regulating glucose metabolism, enhancing insulin sensitivity, and reducing oxidative stress. Data expressed as mean ± SEM showed significant differences (p<0.05) among control, diabetic control, emodin-treated, and metformin-treated groups. Emodin treatment notably improved glucose metabolism and outperformed metformin in reducing insulin resistance. These findings highlight emodin's potential as a therapeutic agent for Type 2 diabetes by targeting insulin resistance, inflammation, and metabolic dysregulation. Emodin holds promise for managing diabetes and its complications effectively.